GNSS signals ionospheric propagation characteristics in space service volume. (30th July 2019) - Lin, Kui; Zhan, Xingqun; Huang, Jihong
In recent years, Global Navigation Satellite System (GNSS) showed a remarkable capability to serve for medium and high earth orbit spacecraft, called space service volume (SSV). However, SSV users face a critical problem of insufficient GNSS signal visibility. In previous studies, the ionospheric signals are usually discarded, which results in a large discrepancy in mission design and system optimisation. In this paper, a three-dimensional ray-tracing method is adopted to analyse signal propagation through the ionosphere. Taking GPS constellation and a GEO user as an example, the principles are validated with a careful simulation. The results show an interesting phenomenon that the bending angle of the signal path and the ionospheric attenuation are very small, and the ionospheric delay is large but eliminable. If the ionospheric signals are considered, the signal visibility and availability will significantly increase, which leads to a shortened maximum outage time for SSV users.